Risk factors for mediastinal lymph node metastasis and lung metastasis in papillary thyroid carcinoma patients: who benefits from preoperative computed tomography? - Yoko Omi; Juro Yanagida; Yusaku Yoshida; Kiyomi Horiuchi; Takahiro Okamoto (Endocrine Journal)
In papillary thyroid carcinoma (PTC) patients with mediastinal lymph nodes (LN) and lung metastases, adding preoperative computed tomography (CT) to ultrasound is useful for planning surgery. We identified risk factors (RFs) for mediastinal lymph node metastasis (MLNM) and lung metastasis in PTC patients. Frequencies of MLNM and lung metastases were compared in 478 patients. Relative risk (RR) was calculated based on RFs. MLNM and lung metastases were detected in 1.2% and 3.3% of patients, respectively. cT3-4, cN1, central LN metastasis, and lateral LN metastasis were RFs for MLNM in all patients (p < 0.05, p < 0.05, p < 0.05, p < 0.01) and older patients (age: ≥55 years) (p < 0.01, p < 0.05, p < 0.05, p < 0.05). cT3-4, cN1, gross extrathyroidal extension, central LN metastasis, and lateral LN metastasis were RFs for lung metastasis in all patients (p < 0.01, p < 0.05, p < 0.01, p < 0.01, p < 0.01, respectively). cN1 and gross extrathyroidal extension, central LN metastasis, and lateral LN metastasis were RFs in older patients (p < 0.01, p < 0.01, p < 0.05, p < 0.01), while lateral LN metastasis was an RF for lung metastasis in those of <55 years of age (younger patients) (p < 0.05). No MLNM was observed in cT1-2cN0 PTC patients, who accounted for 50.5% of patients included in the MLNM analysis. No lung metastasis was present in cT1-2cN0 PTC patients, who accounted for 50.5% of the patients included in the lung metastasis analysis. PTC patients with cT3-4 and cN1 have an increased risk of MLNM and lung metastasis. RFs differed between older and younger patients. Preoperative neck and chest CT are not necessary for PTC patients with ultrasound-diagnosed as cT1-2cN0.